MANUSKRIP ISLAM DI BARAT: KAJIAN DI PERPUSTAKAAN LEIDEN - Ahmad Nabil Amir (Turast: Jurnal Penelitian dan Pengabdian, 2021)
This paper examines the history of manuscript writing and production in the Islamic world and its development in the modern age. He focuses on ancient manuscripts stored in the library of Leiden, the Netherlands, by examining its substantive historical setting, about how it was obtained and brought into Europe, how it was preserved and the initiative to dismantle and remove it. These old manuscripts have left an important legacy and contribution to civilization and are valuable treasures and assets that should be studied and utilized.